Pengembangan instrumen tes berbasis PISA untuk mengukur kemampuan berpikir kritis matematis siswa kelas IX MTS Negeri Binjai - Nst, Fadhilah Ulfah; Sidabutar, Amelia; Gea, Kurnia Mildawati (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research is a development research using formative evaluation development type which consists of 2 stages; (1) priliminary stage which includes self-evaluation and design and (2) prototyping stage which includes expert reviews, one-to-one, small group and field tests. The results of the study indicate that a PISA-based instrument has been successfully developed with quality from the aspects of validity and practicality. The validation results are shown from the content validity by experts who state "the questions can be used without revision" and the validity of the test items with each test item declared "valid" because tcount ≥ ttable in each test item calculation. Practicality can be seen from the student response questionnaire which was achieved with a percentage of 92,36% and the teacher’s response questionnaire which was achieved with a percentage of 100%. Based on the results of data analysis on mathematical critical thinking skills, the average total score was 37.55. This value indicates that the level of mathematical critical thinking ability is included in the low category.